Calcium-binding proteins and calcium function : proceedings of the International Symposium on Calcium-Binding Proteins and Calcium Function in Health and Disease, June 5-9, 1977 / sponsored by the Divisions of Biological and Nutritional Sciences and the New York State College of Veterinary Medicine, Cornell University ; editors, R.H. Wasserman [and others].
Summary goes here